High serum CA19-9 predicts severe cholecystitis in calculous cholecystitis patients - Shouwen Wang; Dachen Zhou; Wanjin Chen; Qi Guo; Liujin Hou; Ruolin Wu; Wei Wang; Muhammad Annus Khan; Muhammad Ahmad; Fan Huang; Meijuan Zheng; Guobin Wang; et al. (BMC Gastroenterology)
Abstract Background CA19-9 is a classical tumor marker and plays an important role in the diagnosis of biliary and pancreatic cancer. However, a few cases reported that the tumor maker CA19-9 is abnormally elevated in patients with calculous cholecystitis, but the relation between severity of calculous cholecystitis and serum CA19-9 level are still unknown. Methods Total 105 calculous cholecystitis patients from first hospital were collected and divided into high serum CA19-9 group(high group, n = 35) and normal serum CA19-9 group(normal group, n = 70). Perioperative data including blood cell count, inflammatory markers, liver function, imaging and operation-related parameters from these patients were collected for analysis and verified with second group of 105 calculous cholecystitis patients from second hospital. Besides, the gallbladder specimens were collected for immunohistochemical staining and mRNA sequencing. Results Abdominal pain occur in more than 90% patients in high group, which is similar with that of normal group. But WBC, neutrophils count, NLR, CRP level and IL-6 level is higher in high group than that of normal group. In addition, the gallbladder wall thickness, the operation duration and the operation conversion rate is also higher in high group, which is verified from second hospital. Higher expression of CA19-9 was found by immunohistochemical staining in gallbladder specimen and more autophagy pathway related genes enriched in high group. Conclusions This study demonstrated that higher level of serum CA19-9 correlates with more severe cholecystitis in calculous cholecystitis patients for the first time, which will provide helpful information for clinical practice and basic research in related field.